Development of Learning Instruments Based on Game-Based Learning Assisted by Baamboozle Educational Game on Digestive System Material to Improve Students' Learning Outcomes - Saroza Nandhini; Rasyidah Rasyidah (IKIP Mataram, 2024)
This study focuses on the development of game-based learning instruments using the Baamboozle educational game for teaching digestive system material to eleventh-grade students. The need for this study arose from observations and interviews conducted with biology teachers at Hang Tuah Belawan Private High School, which revealed that the traditional teaching methods currently employed are ineffective in enhancing student interest and comprehension of complex digestive system material. The research methodology used in this study is the Four-D development model (Define, Design, Develop, Disseminate), which falls under the umbrella of development research or research and development (R&D). Data were collected through interview sheets, expert validation sheets, questionnaires for students and teachers regarding the use of learning instruments, as well as pretest and posttest sheets to evaluate effectiveness. Data analysis was conducted using the Likert scale, and the results were categorized based on the scale's interpretation criteria to conclude the validity, practicality, and effectiveness of the instruments. The findings indicate that the game-based learning instruments developed using Baamboozle games are highly valid, practical, and effective. This study makes a valuable contribution to the advancement of innovative teaching methods that combine educational game technology with complex biological concepts. The implications of this study are significant for future research and practice in educational technology, particularly in terms of enhancing student engagement, promoting the creation of interactive game-based learning content for various subjects, and exploring the long-term effectiveness of game-based learning in science education at the secondary level.